2010
DOI: 10.1111/j.1365-2362.2010.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave velocity and augmentation index, but not intima‐media thickness, are early indicators of vascular damage in hypercholesterolemic children

Abstract: Our findings show that local and systemic arterial stiffness are increased in asymptomatic, normotensive HCh children, suggesting that HCh plays a key role in arterial mechanical impairment since the paediatric age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 41 publications
4
74
1
8
Order By: Relevance
“…Aortic stiffness, measured with carotid-femoral pulse wave velocity, was comparable in patients with FH and their FH-free relatives. Similar data regarding local stiffness assessment by echo-tracking in patients with FH were obtained by Riggio et al [17]. However, unlike our study, they analyzed only the group of children, whereas the control group included only healthy subjects.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Aortic stiffness, measured with carotid-femoral pulse wave velocity, was comparable in patients with FH and their FH-free relatives. Similar data regarding local stiffness assessment by echo-tracking in patients with FH were obtained by Riggio et al [17]. However, unlike our study, they analyzed only the group of children, whereas the control group included only healthy subjects.…”
Section: Discussionsupporting
confidence: 64%
“…There is only one study assessing common carotid artery stiffness by echo-tracking in patients with FH, and this shows that local arterial stiffness is increased in asymptomatic normotensive children with FH, suggesting that hypercholesterolemia plays a key role in arterial mechanical impairment from childhood [17].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, current data suggest childhood BP only variably predicts increased PWV (125)(126)(127). Emerging data suggest that functional changes in large vessels are the earliest detectable findings in children, for example in those with familial hypercholestrolaemia and CKD (128,129).…”
Section: Blood Vesselsmentioning
confidence: 81%
“…Increased arterial stiffness evaluated by applanation tonometry was also reported in children with type 1 diabetes [13], hypercholesterolemia [14], low birth weight [15], end-stage renal failure treated with hemodialysis [16] and after kidney transplantation [17]. In addition, Yu et al showed increased pulse wave velocity in patients with acute post-streptococcal glomerulonephritis [18].…”
Section: Introductionmentioning
confidence: 81%